2018
DOI: 10.12688/f1000research.13990.2
|View full text |Cite
|
Sign up to set email alerts
|

The acid tolerance response and pH adaptation of Enterococcus faecalis in extract of lime Citrus aurantiifolia from Aceh Indonesia

Abstract: Background: The objective of the present study was to evaluate the acid tolerance response and pH adaptation when Enterococcus faecalis interacted with extract of lime ( Citrus aurant iifolia). Methods : We used E. faecalis ATCC 29212 and lime extract from Aceh, Indonesia. The microbe was analyzed for its pH adaptation, acid tolerance response, and adhesion assay using a light microscope with a magnification of x1000. Further, statistical tests were performed to analyze both correlation and significance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
2
7
0
2
Order By: Relevance
“…Fermented fruit peels eco-enzymes are generally acidic with pH ranges from 2.8 to 3.6 [69,70], and this pH itself does not have significant antimicrobial properties against endodontic pathogenic microorganisms [58], including Enterococcus faecalis [71]. This finding is also in line with a study that reported that Enterococcus faecalis was able to tolerate the acidic environment at pH 2.9-4.2 [72].…”
Section: Discussionsupporting
confidence: 55%
“…Fermented fruit peels eco-enzymes are generally acidic with pH ranges from 2.8 to 3.6 [69,70], and this pH itself does not have significant antimicrobial properties against endodontic pathogenic microorganisms [58], including Enterococcus faecalis [71]. This finding is also in line with a study that reported that Enterococcus faecalis was able to tolerate the acidic environment at pH 2.9-4.2 [72].…”
Section: Discussionsupporting
confidence: 55%
“…This suggests that, in CAUTIs of diabetic patients, lactic acid production could confer an advantage to E. faecalis over K. pneumoniae or other species, because some E. faecalis strains can resist and adapt to different pH ranges growing in highly acid conditions (pH 2.9) (Rince et al 2000;Mubarak & Soraya 2018). Moreover, it is well known that growth inhibition of different Gram-negative pathogens in urine occurs at pH 5.0 and below (Kaye 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Enterococci and clostridia have a higher survival rate in different environments, and thus they survived in sludge for a long time even at pH 2.5, but these bacteria could not survive when the pH was lower than 2. It has been reported that the survival of some pathogens can be reduced at pH values lower than 3.5 [ 35 ], but the suppression of enterococci required a pH under 2.5 [ 36 ]. Clostridia, meanwhile, could not survive at a pH below 2 [ 37 ], in contrast with the results of our study ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%